PENGEMBANGAN EDU KOMIK SEBAGAI BAHAN AJAR BERBASIS PENDIDIKAN KARAKTER PADA MATERI INTERAKSI MAHLUK HIDUP DAN LINGKUNGANNYA DI SEKOLAH MENENGAH PERTAMA - Zuli Lailatul Fajriah; Evita Anggereini (BIODIK, 2016)
ABSTRACT. This experiment uses a model of procedural development of ADDIE instructional design. Data were obtained in the form of quantitative data obtained through a questionnaire. The data obtained in the subsequent descriptive-quantitative analysis. Validation by media experts to obtain a score of 60 with a percentage of 93.75% with interpretation of "very good". Validation by matter experts to obtain a score of 74 with a percentage of 92.5% with the interpretation of "very good". Based on the research that has been conducted in small groups with the subject of as many as 12 students gain a percentage of 88.95 were included into the category of "very good". The number of respondents was 427. Judging criteria for the interpretation of the scale 4 with a score range of 393-483 with the results obtained 427 so that the level of its category as very good. Based on the results of these studies indicate that the media edu - comic developed well received by the respondent and was suggested as a learning media on the subject matter of the interaction of living organisms and their environment. Â  Keywords: Edu-comics, Interaction of living beings and the environment.